Rational Design of Peptide-Based Inhibitors Disrupting Protein-Protein Interactions - Wang, Xuefei; Ni, Duan; Liu, Yaqin; Lu, Shaoyong (Frontiers in Chemistry, 2021)
Protein-protein interactions (PPIs) are well-established as a class of promising drug targets for their implications in a wide range of biological processes. However, drug development towards PPIs is inevitably hampered by their flat and wide interfaces, which generally lack suitable pockets for ligand binding, rendering most PPI systems “undruggable”. Here, we summarized drug design strategies for developing peptide-based PPI inhibitors. Importantly, several quintessential examples towards well-established PPI targets such as Bcl-2 family members, p53-MDM2, as well as APC-Asef are presented to illustrate the detailed schemes for peptide-based PPI inhibitor development and optimizations. This review supplies a comprehensive overview of recent progresses in drug discovery targeting PPIs through peptides or peptidomimetics, and will shed light on future therapeutic agent development towards the historically “intractable” PPI systems.